(untitled) (EAAE Annual Conference Proceedings, 2023)
We thank all speakers, respondents, moderators, student volunteers, colleagues and administrative staff from Politecnico di Torino, Department of Architecture and Design who provide the venue and made this event possible, to our general sponsor Velux.